Effect of Bio-stimulators Compounds on Quantitative and Qualitative Yield of German Chamomile (Matricaria recutita L.) - H Golzadeh; A Mehrafarin; H Naghdi Badi; F Fazeli; A Qaderi; N Zarinpanjeh (Institue of Medicinal Plants, ACECR, 2012)
Background : In order to ecological agriculture, application of bio-stimulators compounds can be increase the quantitative and qualitative yield of crops in company with reducing environmental stresses.   Objective : To determine the effects of bio-stimulators compounds on quantitative and qualitative yield of German chamomile (Matricaria recutita L.), this experiment was conducted.   Methods : This study was done in research farm of ACECR, Institute of Medicinal Plants in a randomized complete block design with three replications and ten treatments in 2010. The treatments were C (Control/no fertilizer), CF (Chemical fertilizer), A1 (Aminolforte 0.75 L.ha-1), A2 (Aminolforte 1.5 L.ha-1), K1 (Kadostim 0.75 L.ha-1), K2 (Kadostim 1.5 L.ha-1 ), H1 (Humiforte 0.75 L.ha-1), H2 (Humiforte 1.5 L.ha-1), F1 (Fosnutren 0.75 L.ha-1), and F2 (Fosnutren 1.5 L.ha-1).   Results : The results showed that the different treatments had significant effects on plant height, capitule diameter, capitule number per plant, fresh and dry matter yield of capitule per hectare, essential oil yield per hectare, chamazulene content, total flavonoid content (p<0.01) and plant harvest index (p<0.05). Also, the treatments didn't have significant effects on plant water content. Conclusion : Application of bio-stimulators could be increased the quantitative and qualitative yield of German chamomile. However, treatments of A2 and F2 (Aminolforte and Fosnutren 1.5 L.ha-1) were the best treatments in respect of yield of capitule and essential oil per hectare. Also, the application of the bio-stimulators can lead to increasing crop production in company with minimizing of environmental pollution and sustainable agriculture.